(untitled) (Comparative Professional Pedagogy, 2023)
This paper represents an attempt to conduct research of modern tendencies, strategies and directions of education development within the perspective of the European Union. The main aim of the research is to learn more about the policy of the European Union concerning the general development of education, forming of favorable educational environment and protecting the rights of its citizens for education and professional development. The study relies on the theoretical methods of scientific research. The main source of the analysis, generalization and description is represented by various documents, recommendations, programmes, and guidelines issued by the European Commission, the European Pillar of Social Rights, the European Educational Area, the European Research Area, the European Skills Agenda, Europe 2020. In the course of the study, the works of foreign researchers have been analyzed, which helped to view the topic of interest from different perspectives. The results of the study highlight the fact that the sphere of education has undergone its major changes due to the circumstances caused by the pandemic. In Ukraine, the great number of obstacles in education has appeared due to war, which made qualitative education impossible for many Ukrainians. Because of this, it is certainly important to study foreign experience in order to develop new working schemes and models for the sake of keeping education abreast of time and being in line with students’ and teachers’ needs. In the result of the conducted research, it is found that the European Commission has managed to develop a programme to support the future of its education. The main tendencies, strategies and priorities of the European Union concerning the further development of education are represented and described. Key competences and basic skills for people’s personal and professional development throughout life developed by the European Commission and EU Member States are analyzed.